Neutrophil Derived Cathepsin G Induces Potentially Thrombogenic Changes in Human Endothelial Cells: a Scanning Electron Microscopy Study in Static and Dynamic Conditions - Kolpakov, Valeri; D'Adamo, Maria Cristina; Salvatore, Lorena; Amore, Concetta; Mironov, Alexander; lacoviello, Licia; Donati, Maria Benedetta (Thrombosis and Haemostasis, 1994)
Activated neutrophils may promote thrombus formation by releasing proteases which may activate platelets, impair the fibrinolytic balance and injure the endothelial monolayer.We have investigated the morphological correlates of damage induced by activated neutrophils on the vascular wall, in particular the vascular injury induced by released cathepsin G in both static and dynamic conditions.Human umbilical vein endothelial cells were studied both in a cell culture system and in a model of perfused umbilical veins. At scanning electron microscopy, progressive alterations of the cell monolayer resulted in cell contraction, disruption of the intercellular contacts, formation of gaps and cell detachment.Contraction was associated with shape change of the endothelial cells, that appeared star-like, while the underlying extracellular matrix, a potentially thrombogenic surface, was exposed. Comparable cellular response was observed in an “in vivo” model of perfused rat arterial segment. Interestingly, cathepsin G was active at lower concentrations in perfused vessels than in culture systems. Restoration of blood flow in the arterial segment previously damaged by cathepsin G caused adhesion and spreading of platelets on the surface of the exposed extracellular matrix. The subsequent deposition of a fibrin network among adherent platelets, could be at least partially ascribed to the inhibition by cathepsin G of the vascular fibrinolytic potential.This study supports the suggestion that the release of cathepsin G by activated neutrophils, f.i. during inflammation, may contribute to thrombus formation by inducing extensive vascular damage.